Real-Time Software and Hardware System for Verification of Settings of Digital Relay Protection and Automation; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Andreev M. V. Mikhail Vladimirovich (2020, 2020)
Title screen